Digitalisasi Usaha Pada Pelaku UMKM dan IKM Melalui Google Bisnis dan Aktivasi QRIS di Kelurahan Limpomajang, Kabupaten Wajo - Andi Djemma, Siardin; Nurman Dai Basri; Baso Muhammad Yassir; Muh Zhali (Compile Journal of Society Service, 2025)
Community service is one form of implementation of the Tri Dharma of Higher Education, which includes education, research, and community service. This article discusses the digitalization of MSMEs and SMEs in Limpomajang Village, Majauleng District, Wajo Regency. The activities focused on creating Google Business Profiles and activating QRIS (Quick Response Code Indonesian Standard) for business actors as the first step towards digitalization. This program aims to increase business visibility so that consumers can easily find it through Google Maps and provide a more practical non-cash payment system. The results of the activities showed a positive impact, namely increased market reach and ease of transactions, although there are still obstacles such as limited digital knowledge, internet access, and consumer habits that prefer to use cash. Thus, this simple digitalization is an effective step in strengthening the competitiveness of MSMEs and SMEs at the local level.